Genetic analysis in intra- and inter-specific crosses of tree willows - Choudhary, Punit; Singh, N.B.; Verma, Archana (The Indian Journal of Genetics and Plant Breeding, 2016)
Twenty one full-sib families derived from intra- and interspecific controlled crosses were analysed to study different genetic parameters. Estimates of the general combining ability (GCA) variance were found to be less than the specific combining ability (SCA) variance for all the parameters. The dominance variance was more than the additive variance for all the parameters studied. The degree of dominance ranged between 1.73 (per cent successful crosses) and 5.35 (% germination). Moderately high (0.42 for % successful crosses) to low (0.15 for seed per capsule) narrow sense heritibilities and high heritability in broad sense (0.74 to 0.99) for per cent successful crosses and seeds per catkin was recorded. GCA effects were positive and significant for S. tetrasperma (TFB), S. tetrasperma (TWE) and S. tetrasperma (LNM) male parents for all the parameters while S. alba (SE- 63-007) exhibited significantly positive effects for number of seeds/catkin. Among females, S. tetrasperma (LP), S. tetrasperma (LNF) and S. tetrasperma (LN) depicted positive and significant GCA effects for number of seeds/ catkin and per cent germination, respectively whereas crosses, S. matsudana (PN-227) x S. alba (Kashmiri) and S. tetrasperma (LNF) x S. tetrasperma (LNM) exhibited positive and significant SCA effects for per cent successful crosses. Cross S. matsudana (PN-227) x S. alba (Kashmiri) showed positive significant SCA effects for number of seeds/ capsule